Exploring the Nexus of Maqasid Shariah and Economics - Nadia Nurul Izza; Ihsanul Ikhwan (Tamkin Journal, 2023)
This study attempts to map research related to maqasid shariah on economics published by Scopus indexed journals from 2006 to 2023. NVivo 12 Plus is used to conduct thematic studies and the frequency is used to evaluate 118 publications in scientific literature. The results of the study found that the number of publications fluctuated from year to year related to research on maqasid shariah on economics which indicated that this topic was an interesting topic and should continue to be developed. In addition, various focus discussions and cluster analyzes that describe research lines in maqasid sharia research on economics include (1) maqasid sharia in banking, (2) maqasid sharia in financial issues, and (3) maqasid sharia in economic topics in general. This research can be used as a starting point for experts to build graphic visualizations of maqasid shariah on economic research patterns in published scientific research.